Pengembangan Papan Partikel dari Limbah Kayu Meranti Menggunakan Perekat Damar - Akram Akram; Samsul Rizal; Syifaul Huzni (Jurnal Teknik Mesin Unsyiah, 2014)
Particle board is a product of the utilization of waste wood processing that can be used in a variety of buildings and other constructions. Particle board products generally produce formaldehyde emissions that can harm human health. Reducing emissions of formaldehyde, environmentally friendly adhesive should be used, ie Damar (Shorea javanica). In this study, the adhesive resin used as an adhesive for wood particle boards Meranti. This study aims to develop a particle board from Meranti wood waste using adhesive resin, and then to determine the effect of the use of the adhesive resin particle board to physical strength and mechanical wood powder particle board. Making specimens following the ISO Standards No.. 03-2105 - 2006 through print method pressure of 1.33 MPa. Particle size of wood used (0.315 to 5 mm), mixed with a resin weight percentage of 5%, 10%, 15% and 20%. Heating temperature is 150 ° C for 15 minutes. Obtained from testing the tensile strength of 0516 MPa highest density value 0.989 g/cm3. The results obtained from specimens that have adhesive resin composition of the Meranti wood particles with a ratio of 20:80 with a density value of 0.989 g / cm, while for the weight gain and the development of thick generate value by 42%, and 27% lower than at the other test specimens. While the value of the modulus of elasticity for the same composition was 1642 MPa. Based on the percentage, the higher the use of resin will be obtained, the value of tensile strength, modulus of elasticity and the higher density. While the value of water content and the development of diminishing thickness.